Ground penetrating radar system using OFDM technology - Mohamed Hassan, Ahmed Abbas; Abdul Aziz, Normaziah ([s.n], 2012)
Ground Penetrating Radar (GPR) can be employed in an array of civil and military applications such as Nondestructive testing (NDT) of structures and pavements, Earth sciences, and Studying of soils for Oil excavation. Multiple lines of GPR data can be used to construct three-dimensional images for different purposes of exploratory and detection missions. However, high expertise is needed to effectively construct and interpret GPR data. For this reason, DSP engines have been recently incorporated into GPR devices to facilitate real time and valid interpretation of GPR data. Moreover, the penetration range of GPR is significantly reduced in clayey soil and in high conductivity medium in general. DSP engines can enhance the quality of data collected in this type of soil and properly extend the penetration range. This research proposal is directed to implementing OFDM engine on ultra-wideband (UWB) technology to improve the performance of GPR systems and enable its application to a wider array of non-destructive, civilian applications.